Immune Response of Thalassemia Major Patients in Indonesia with and without Splenectomy - Teny T Sari1; Djajadiman Gatot; Arwin A.P. Akib; Saptawati Bardosono; Sri R.S. Hadinegoro; Alida R Harahap; Ponpon S Idjradinata (Acta Medica Indonesiana)
Aim: to describe non-spesific and specific immune response profile in Indonesian thalassemia major with and without splenectomy. Methods: this study was held at Thalassaemia Centre, Cipto Mangunkusumo Hospital Jakarta on September 2013 – February 2014. A comparative cross sectional study was conducted in healthy, thalassemia major aged more than 12 year and seronegative HIV. They were matched in age and sex for splenectomised and non-splenectomised groups, analysing the non-spesific immune response (neutrophil count and phagocytosis) and specific immune response (count and function of cellular immunity). Infection episodes were also analized as immune response in vivo parameter. Results: splenectomised thalassemia major showed increased neutrophil count but significantly decreased non-spesific immune response (neutrophil phagocytosis). Spesific immune response of splenectomised group presented significantly higher absolute lymphocyte, lymphocyte T, CD4+ and CD8+ counts compared to non-splenectomised thalassemia major (p<0.05). Ratio CD4+/CD8+ were similar in these groups. Serum marker of activated cellular imunity function (IL-2 and TNF-α) were similar among two groups. Mild infection episodes on splenectomised and non-splenectomised group were 2.02 (ranged 0 to 12) times and 0.81 (ranged 0 to 8) times (p=0.004), respectively. Severe infection on splenectomised group were sepsis for 2 weeks and diarrhea for 1 week, whereas on non-splenectomised group was typhoid fever for 4 days. Conclusion: there were significant differences on immune response among thalassemia major patients. Splenectomised thalassemia major showed a greater degree of susceptibility to infections than non-splenectomised thalassemia major.